-116-6g=-32

Simple and best practice solution for -116-6g=-32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -116-6g=-32 equation:


Simplifying
-116 + -6g = -32

Solving
-116 + -6g = -32

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '116' to each side of the equation.
-116 + 116 + -6g = -32 + 116

Combine like terms: -116 + 116 = 0
0 + -6g = -32 + 116
-6g = -32 + 116

Combine like terms: -32 + 116 = 84
-6g = 84

Divide each side by '-6'.
g = -14

Simplifying
g = -14

See similar equations:

| 8-2x=2c | | 6z=17 | | 5y+35=0 | | 6x^2-32x+32=0 | | 47=-(x+11) | | 10x+1.7=-3.5 | | 4(m+3)+7=m+19 | | 2x+10=4x | | -15=.375(x+8) | | 9x-21=3(g-7)+6t | | 2X+8X-7X+10=22 | | 2.2x+1=3.2 | | 3(4k+14)=10x-2(g-7) | | 10v^2+4v-22=0 | | d-1=-13 | | 10v^2+4-22=0 | | 3(x+8)=9 | | 4x-4=-4 | | 8(9-x)=-72 | | 2y^2-16y+20=0 | | 1r^2-12r-133=0 | | g(12)=3x+6 | | 5r-3(r+6)=24 | | 4x+x-2=4x+6 | | g(-1)=3x+6 | | 2c-3=76 | | g(0)=3x+6 | | 2-(5-w)+3(-2w)= | | 2n+5=4n+2-n | | 3p^2+3p-36=0 | | 9-30=6-p | | X+6(3)=42 |

Equations solver categories